Cell-specific electrical stimulation of human retinal neurons assessed by pupillary response dynamics in vivo. (September 2022) - Jung, Ronja; Kelbsch, Carina; Wilhelm, Helmut; Wilhelm, Barbara; Strasser, Torsten; Peters, Tobias; Kempf, Melanie; Kortüm, Friederike; Pohl, Lisa; Stingl, Krunoslav; Stingl, Katarina
Abstract: Studies on the electrical excitability of retinal neurons show that photoreceptors and other cell types can be selectively activated by distinct stimulation frequencies in vitro . Yet, this principle still needs to be validated in humans in vivo. As a first step, this study explored the frequency preferences of human rods by means of transcorneal electrostimulation (TES), using the electrically-elicited pupillary responses (EEPRs) as an objective readout. The stimulation paradigm contained a 1.2 Hz sinusoidal envelope, which was superimposed on variable carrier frequencies (4–30 Hz). These currents were delivered to one of the participant's eyes via a corneal electrode and consensual pupillary reactions were recorded from the contralateral eye. The responsiveness of the retina at each frequency was assessed based on the EEPR dynamics. Differences between healthy participants and patients with retinitis pigmentosa were evaluated to identify the preferred frequency range of rods. The responsiveness of healthy individuals revealed a clear peak around 6–8 Hz. In contrast, the pupillary responses of patients were significantly reduced in the lower frequency range. These findings suggest that the responses in this frequency bin were selectively mediated by rods. This work provides evidence that different retinal cell types can be selectively activated via TES in vivo, and that this effect can be captured noninvasively using EEPRs. This knowledge may be exploited for the diagnostics and therapy of retinal diseases, e.g., to design cell-specific functional tests for the degenerating retina, or to optimize stimulation paradigms which are currently used by retinal prostheses. Highlights: Sinusoidal currents of 4–30 Hz were applied to volunteers via corneal electrodes. Pupillary responses served as an objective readout for the retinal responsiveness. Healthy participants displayed elevated responsiveness in the 6–10 Hz range. Patients with Retinitis Pigmentosa showed reduced responses in the 6–10 Hz range. The difference suggests that rods are tuned to low-frequency stimulation.